3(M-2)-2M=5

Simple and best practice solution for 3(M-2)-2M=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(M-2)-2M=5 equation:


Simplifying
3(M + -2) + -2M = 5

Reorder the terms:
3(-2 + M) + -2M = 5
(-2 * 3 + M * 3) + -2M = 5
(-6 + 3M) + -2M = 5

Combine like terms: 3M + -2M = 1M
-6 + 1M = 5

Solving
-6 + 1M = 5

Solving for variable 'M'.

Move all terms containing M to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 1M = 5 + 6

Combine like terms: -6 + 6 = 0
0 + 1M = 5 + 6
1M = 5 + 6

Combine like terms: 5 + 6 = 11
1M = 11

Divide each side by '1'.
M = 11

Simplifying
M = 11

See similar equations:

| 2k(k+7)=2k^2+2(7)k | | 0.10x+0.05y=5.75 | | 5x+20=3x-20 | | 29x-50=22-2x | | 5x-9=82-8x | | 2(x-1)=3x-8 | | 7/8x-5/8=8 | | 3x^3-108=0 | | (x+2)(x+2)-3x-6=0 | | 4(n-5)=4 | | 26x+21=(-39x)-10 | | x+x+20+(210-3x)=180 | | 4.46x+8.92=17.84 | | 4.46+8.92=17.84 | | 15g+45=5[k-10] | | 15g+45=[k-10] | | (2+4)2= | | 3w-12=3w-12 | | y=10/17-x | | log(4)x+log(4)(x+12)=3 | | x^2+y^2+4x-10y=20 | | 4X-16=16X | | log(3)(2x+1)+log(3)(x+8)=3 | | p(x)=3x-5 | | Log(3)(3x+4)=2 | | Log(3)(3x+4)=-2 | | 4(x+1)(x+1)=2(x+1)(2x-3) | | (m-2)+(m-5)+(m-7)+2+6+5+7=m | | 3xsquare-5x+2=0 | | 2z^2-3=-z-2 | | Log(3)(3x-4)=2 | | 9cosx+6sinx=10 |

Equations solver categories